2022
DOI: 10.1155/2022/4690140
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Low Carbon Economy Assessment in China Using the Super‐SBM Model

Abstract: This review proposes a performance evaluation system of low-carbon economic development based on multiobjective analysis in low-carbon environment. This is a modeling method combining super efficiency and relaxation-based measurement model (super-SBM model), which can effectively measure green innovation efficiency with unexpected outputs and traditional innovation efficiency without unexpected outputs. Using the Malmquist–Luenberger index method to dynamically analyze the efficiency of green innovation, a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…On this basis, the evaluation indicator system is elaborated according to the specific requirements of the different levels. It also defines the scope of the evaluation indicators, clarifies the interlinkages between indicators, and improves the data acquisition and processing to ensure that the evaluation indicator system is scientific and operational, providing a scientific evaluation method and decision support for the sustainable development of low carbon cities [9][10].…”
Section: Design Stepsmentioning
confidence: 99%
“…On this basis, the evaluation indicator system is elaborated according to the specific requirements of the different levels. It also defines the scope of the evaluation indicators, clarifies the interlinkages between indicators, and improves the data acquisition and processing to ensure that the evaluation indicator system is scientific and operational, providing a scientific evaluation method and decision support for the sustainable development of low carbon cities [9][10].…”
Section: Design Stepsmentioning
confidence: 99%
“…Chinese mouths are very large, but there is always an unbalanced system between the manufacturing system and the trading system of the textile industry, that is, oversupply. In order to obtain relevant profits, it is necessary to export a lot of textile products [14] Part of the textiles is the domestic resources produced and manufactured, many of which consume limited resources. The state has introduced the current policy of accelerating the replacement of some backward production capacity enterprises and technologies, but the corresponding problems such as outdated machinery and equipment, low production and manufacturing efficiency, and insufficient staffing have not been dealt with in essence, which limits printing and dyeing: the development of the industry and the pace of China's development trend towards a "green and low-carbon economy".…”
Section: High-energy Consumptionmentioning
confidence: 99%
“…From the systematic literature search presented, it can be ascertained that there is a lack of scholarly attention on the topics related to LCE using the DEA methodology in Europe. The majority of the studies found in the literature, which focused on this topic using the DEA methodology are mostly circumscribed to China and employ the SBM model (e.g., [5][6][7][8][9]-see Table 1. In effect, nonparametric approaches, such as DEA, can be particularly useful when contrasted with other evaluation approaches because they allow handling a multitude of criteria in efficiency assessment and do not require a specific functional form.…”
Section: Literature Reviewmentioning
confidence: 99%